P2_7 Magnetic Mayhem - Phillips, Mark; Griffiths, Tom; Herlingshaw, Katie; Vasudevan, Duleep (Physics Special Topics, 2014)
This study calculates the increase in solar wind pressure required to compress the nose of the magnetopause of the Earth, down to its surface. It is found that the solar wind pressure would have to increase by at least a factor of to do this.